Perforated Duodenal Diverticulum Treated Conservatively: Another Two Successful Cases - Jad A. Degheili; Mohammed H. Abdallah; Ali A. Haydar; Ahmad Moukalled; Ali H. Hallal (Case Reports in Surgery)
Diverticula of the duodenum proceed those of the colon in respect to frequency of location. Incidence at times of autopsy ranges from 15 to 23%. Despite the fact that more than 90% of duodenal diverticulum cases are asymptomatic, complications if they do occur can be calamitous. Perforation is one of these rare complications. Surgical intervention has always been the mainstay for symptomatic/complicated duodenal diverticula, but with the advancement of imaging, medical treatment, and proper intensive observation, conservative treatment came forth. We hereby present two cases of duodenal diverticula, complicated by perforation and fistulization into the retroperitoneal cavity, both treated conservatively by Taylor’s approach of upper gastrointestinal tract perforation. Review of other cases of duodenal diverticulum perforation has also been presented.